Răspuns :
a). [tex] \frac{x-1}{ 125*x^{3} } + \frac{x+1}{125*x^{3} } = \frac{x-1+x+1}{125*x^{3} } = \frac{2x}{125*x^{3} } = \frac{2}{125* x^{2} } [/tex]
b) [tex] \frac{x+1}{125* x^{3} } - \frac{x-1}{125* x^{3} } = \frac{x+1-x+1}{125* x^{3} } = \frac{2}{125* x^{3} } [/tex]
c) [tex] \frac{x-1}{125* x^{3} } * \frac{x+1}{125* x^{3} } = \frac{(x-1)*(x+1)}{15625* x^{6} } = \frac{ x^{2}-1 }{15625* x^{6} } [/tex]
d). [tex] \frac{x-1}{125* x^{3} } * \frac{125* x^{3} }{x+1} = \frac{x-1}{x+1} [/tex]
e). [tex] \frac{x+1}{125* x^{3} } * \frac{x+1}{125* x^{3} } = \frac{ x^{2} +2x+1}{15625* x^{6} } [/tex]
b) [tex] \frac{x+1}{125* x^{3} } - \frac{x-1}{125* x^{3} } = \frac{x+1-x+1}{125* x^{3} } = \frac{2}{125* x^{3} } [/tex]
c) [tex] \frac{x-1}{125* x^{3} } * \frac{x+1}{125* x^{3} } = \frac{(x-1)*(x+1)}{15625* x^{6} } = \frac{ x^{2}-1 }{15625* x^{6} } [/tex]
d). [tex] \frac{x-1}{125* x^{3} } * \frac{125* x^{3} }{x+1} = \frac{x-1}{x+1} [/tex]
e). [tex] \frac{x+1}{125* x^{3} } * \frac{x+1}{125* x^{3} } = \frac{ x^{2} +2x+1}{15625* x^{6} } [/tex]